Gender And Workplace Associated With Psychosocial Status Of Nursing Population In Third Month Covid-19 Outbreak - Hapsah Hapsah; A Nur Anna AS; Rasmawati Rasmawati; Wahyuni Wahyuni; Basmalah Harun (Universitas Padjadjaran, 2021)
Health care professionals have a higher risk of contracting Covid-19 with high stress, overwork, sometimes without proper training and personal protective equipment. Gender, occupation and workplace were factors affected to cope stress ability in person daily life. Aim of this study was to identify association between gender and workplace with psychosocial status on 920 mental health nursing seminar participants in the first three months of Covid-19 outbreak in various Indonesian regions. Accidental sampling was conducted an hour before the Indonesian National Nurses Association of South Sulawesi started the seminar with The Self-Reporting Questionnaires (SRQ29) online form with informed consent. There were 920 of 1500 participants filled the form. Variable association was analyzed by using Pearson Chi Square and Fisher Exact Test. The results show that based on gender, women significantly dominated anxiety symptom, somatic symptom, decreased energy symptom and post traumatic stress symptom Workplace significantly associated with depression symptom, cognitive symptom, psychotic symptom and post traumatic stress symptom which dominate in college. Gender and workplace were associated with psychosocial symptom. Therefore, it is essential for further research to arrange strategies for minimizing those symptoms.